Real Options Illustrated - Peters, Linda (SpringerBriefs in Finance,, 2016)
This book explains the standard Real Options Analysis (ROA) literature in a straightforward, step by step manner without the use of complex mathematics. A lot of ROA literature is described through partial differential equations, probability density functions and simulation techniques, all of which may be unconvincing in the applicable qualities ROA possesses. Using this book, the reader will have a better grasp about how ROA works and will be able to provide his or her judgment about ROA, since all the basics, as well as its positive and negative qualities, are discussed. Real Options Illustrated provides practitioners with a real options framework and encourages readers to study the methodology using the in-depth explanations. This introduction to ROA is sufficient to equip readers with ROA basics, enabling them to perform future independent research. From this book, readers can judge whether ROA is of any value to their field.